Understanding acute pancreatitis in end-stage renal disease: unraveling etiologies, clinical presentations, management strategies, and complications—a narrative review - Chloe Lahoud; Zeina Morcos; Ryan Njeim; Mark Tawfik; Taimur Aslam; Suzanne El-Sayegh (Journal of Pancreatology)
Acute pancreatitis (AP) is a common disease with defined diagnostic criteria, radiological findings, and management guidelines. Patients with end-stage renal disease (ESRD) are at an increased risk of developing AP. The diagnosis of AP in ESRD is challenging, and the clinical presentation may mimic other pathologies. Moreover, the impact of AP on the overall morbidity and mortality in ESRD patients warrants a tailored therapeutic approach. We conducted a literature search for published manuscripts on AP and ESRD up to November 2023 in several databases such as Google Scholar and PubMed, and employed the following search terms: “acute pancreatitis,” “pancreatitis,” “end-stage renal disease,” “hemodialysis,” “peritoneal dialysis,” “diagnostic criteria,” “etiology,” “presentation,” “management,” “complication,” “prognosis,” “mortality.” Qualitative and quantitative data were both extracted. This article reviews current evidence-based literature about the etiology and clinical presentation of AP in ESRD. It sheds the light on the current clinical studies that reflect beneficial management strategies as well as complications of AP in ESRD. Patients with ESRD are more likely to develop AP and subsequently severe pancreatitis with high mortality rates compared to the general population. The etiology of AP in ESRD is multifactorial and management is focused on pain control, early nutritional support and most importantly maintaining a fluid balance. While existing research has shed light on certain aspects of AP in ESRD, additional literature focused on this topic is required to foster a deeper and broader understanding of AP in ESRD.